Satisfaction levels of hospitalized patients in a University Hospital in Istanbul [İstanbul'da bi̇r Tip Fakültesi̇ Hastanesi̇nde yatan hastalarin memnuni̇yet düzeyi̇] - (:unkn) unknown (My University, 2008)
Objective: Patient satisfaction is very important as a quality criterion in health care services. Patient satisfaction outcomes are important in quality assessments, shaping and managing health care services. The aim of this study was to determine the satisfaction level of hospitalized patients and the associated factors in Marmara University School of Medicine. Method: The study was designed as cross-sectional. Face to face interviews were conducted with 135 patients who were hospitalized during February 2006. The questionnaire included 61 questions which were prepared in the light of the existing literature. Results and Conclusion: Among the 155 hospitalized patients, 135 (87.09%) participated in the study. 64.5% of the participants reported satisfaction regarding the general hospital care. The most frequent factor for preferring this hospital was related to social insurance and consignment (42.2%). 84.6% of the participants reported that they would again prefer this hospital in the future and 70.7 %of them reported that they would recommend this hospital to their relatives and friends. There was a statistically significant relation between the general satisfaction level and the hospital personnels' attitudes as well as the physical conditions of the hospital (p<0.05). There were also statistically significant relations between the services, the cleaning of the rooms and the doctors' skills.
Keywords: Hospital; Hospitalized patient; Quality; Satisfaction